The mechanism of drone seeding technology: a review - Marzuki, Omar Faruqi; Ellie, Teo Yih Lih; Mohd Rafie, Azmin Shakrine (Malaysian Forester, 2021)
The utilization of drone in various fields such as agriculture, reforestation and seaport is a valuable addition. Aligning the current technology advancement and The Fourth Industrial Revolution (IR 4.0), reforestation and agriculture are integrating drone technology into their ecosystem. As illegal rapid deforestation is increasing and there is a need to replant trees in order to prevent soil erosion, reduce fire risks as well as restore wildlife habitats, reforestation using drone seeding have been explored. Agricultural drone can provide fast seed sowing, hence reducing the working time. This paper reviews the recent advancement in drone mechanism specifically for seeding and planting.